INFLUENCE OF BIG DATA TECHNOLOGY, ASSET STRUCTURE AND DIVIDEND POLICY ON COMPANY VALUE - Ni Luh Putu Wulan Apriyani; Gede Juliarsa (Adisam Publisher, 2025)
The role of the Indonesia Stock Exchange is as an investment vehicle, also as a means for companies to raise additional capital, especially for companies going public. If the shares being traded have a high prospective price, shareholders are willing to invest their capital. A company's share price is a good indicator of its high company value; the higher the share price, the greater the company value, and vice versa. This study aims to assess the impact of big data technology, asset structure, also dividend policy on firm value. Companies listed on the Indonesia Stock Exchange between 2019-2021 made up the study's population. The total sample analyzed in this study was 59. The sample companies were chosen utilizing purposive sampling analysis technique. Multiple linear analysis techniques are the data analysis method employed. The outcomes of this study show that asset structure as well as dividend policy impacted firm value, and big data technology has no impact on firm value. The implications of this study are theoretically able to support the resource-based view theory, stakeholder theory, also signal theory which are used as the basis for preparing hypotheses, namely the effect of big data technology, asset structure, as well as dividend policy on firm value, and Practically this study can be utilized as additional information, input and consideration for firms.